Penurunan tingkat cacat p-tank di line assembling 4 alumunium radiator dengan metode PDCA: Studi Kasus di PT. Denso Indonesia - Umar Alfyanto (Universitas Mercu Buana, 2019)
The The high competition between products requires companies to provide the best for their consumers. Quality is one guarantee that must be given and fulfilled by the company to customers. The purpose of this study was to analyze the causes of P-tank defects and recommend countermeasures to prevent the recurrence of P-tank defects in the assembly line 4 of the Aluminum Radiator division using the PDCA method. Case studies carried out at PT. Denso Indonesia for the period January 2018 - March 2018. Based on the research and data collection in the field it was found that the p-tank NG level was around 0.7 percent and be reduced to 0.4 percent.